2013
DOI: 10.1371/annotation/bb25e7cb-12f7-42e4-9d26-07b9bda87ecc
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Gauging the Threat: The First Population Estimate for White Sharks in South Africa Using Photo Identification and Automated Software

Abstract: South Africa is reputed to host the world's largest remaining population of white sharks, yet no studies have accurately determined a population estimate based on mark-recapture of live individuals. We used dorsal fin photographs (fin IDs) to identify white sharks in Gansbaai, South Africa, from January 2007 -December 2011. We used the computer programme DARWIN to catalogue and match fin IDs of individuals; this is the first study to successfully use the software for white shark identification. The programme p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Although there is scientific debate on the South African white shark population's size, all population estimates are consistently low, ranging from 500 to 2000 individuals (Towner et al, 2013;Andreotti et al, 2016;Andreotti et al, 2017;Irion et al, 2017). In South Africa, white sharks are captured in shark nets and on drumlines along the KwaZulu-Natal (KZN) coast as part of a bather protection program (Dudley and Simpfendorfer, 2006;Rigby et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is scientific debate on the South African white shark population's size, all population estimates are consistently low, ranging from 500 to 2000 individuals (Towner et al, 2013;Andreotti et al, 2016;Andreotti et al, 2017;Irion et al, 2017). In South Africa, white sharks are captured in shark nets and on drumlines along the KwaZulu-Natal (KZN) coast as part of a bather protection program (Dudley and Simpfendorfer, 2006;Rigby et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This migratory behavior supports the use of a mark-recapture framework for estimation of population parameters at coastal sites . Several studies have demonstrated that the pattern on the trailing edge of the white shark first dorsal fin is stable over many years and can be used as a means of identifying individuals, i.e., serves as a natural "mark" (Gubili et al, 2009;Anderson et al, 2011;Towner et al, 2013). The population trend remains unknown in central California although interpretations of catch per unit effort data of young of the year white sharks in Southern California have been taken to suggest an increasing trend in the smaller length classes (<2 m) (Lowe et al, 2012).…”
Section: Introductionmentioning
confidence: 99%